Hubungan Peran Ketua Tim dengan Kinerja Perawat dalam Dokumentasi Asuhan Keperawatan di Rumah Sakit Jiwa Provinsi Jambi - Fithriyani Fithriyani; Miko Eka Putri (Universitas Baiturrahim, 2021)
The quality of service can be determined from the performance of the nurse in providing nursing care. The success of the team method in carrying out the nursing process is determined by the ability of the team leader to assign tasks to team members and direct work to the team. This study aims to knowing the relationship between the role of the team leader and the performance of nurses in documenting nursing care at the Jambi Provincial Psychiatric Hospital. A quantitative method with a cross-sectional survey using self-administered questionnaires The sampling technique was total sampling so that the sample size was 106 nurseswith analysis using the chi square test. The data were analyzed using statistical software. This study investigates the role of team leaders and nurses' performance in documenting nursing care. the role of the team leader in documenting nursing care was 54.1% good. the performance of nurses in documenting nursing care was 53.2% good. The statistical test results showed that the p value (0,000) <0.05, which means that there is a significant relationship between the role of the team leader and the performance of nurses in nursing care documentation.This significant relationship explains that the role of the team leader will have a good influence on the documentation of nursing care carried out by the nurse in charge